Diseño arquitectónico de un centro de desarrollo local con criterios bioclimáticos en el cantón Vinces - Chamba Cuzme, Jhosue Andres (2025)
The present research work is based on the application of five bioclimatic criteria in the Design of a Local Development Center in the Vinces Canton, through which it seeks to optimize the use of resources and adapt to both the urban context and the climatological scenario that it presents since said canton has high temperatures and humidity. The development of the research begins with the analysis of the historical urban context to learn about the existing social, economic and cultural demand, in addition to analyzing in detail the climate it has, so based on said diagnosis that make up a whole, five key bioclimatic strategies for the design are proposed, such as: orientation of the building, natural ventilation, adequate materials, collection of solar energy and the use of vegetation to improve thermal comfort..........